Physical activity and coronary risk indicators in employees from University Hospital of Londrina - Porto, Denilson Braga; De Paulo Filho, Luiz Antônio; Fernandes, Rômulo Araújo [UNESP] (Universidade Estadual de Maringa, 2011)
The aim of this study was to investigate the association between physical activity and indicators of coronary risk in employees from University Hospital of Londrina. The sample consisted of 400 employees from 20-67 years, comprising 64.8% women and 35.3% of men. We applied the short version of the international physical activity questionnaire (IPAQ) and investigation of coronary risk proposed by the Michigan Heart Association. It was found that 64.3% of respondents presented risk of overweight/obesity. As for physical activity it was found that 64.5% of the employees are irregularly active. An association between increased physical activity practice and lower coronary risk was found, especially in men. In conclusion, we found a high risk of cardiovascular disease, and a high proportion of irregularly active subjects and that higher physical activity practice is associated with lower risk, however, this association occurs differently between the sexes.
Prática de atividade física e indicadores de risco coronariano de servidores do Hospital Universitário de Londrina
Keywords: Coronary disease; Motor activity; Questionnaires